Acceptance of LNG as an alternative fuel: Determinants and policy implications. (September 2018) - Pfoser, Sarah; Schauer, Oliver; Costa, Yasel
Abstract: The transport sector causes substantial greenhouse gas emissions and is responsible for the climate change and global warming. Introducing liquefied natural gas (LNG) as an alternative fuel for heavy-duty and long distance transport is an important strategy to increase the sustainability of the transport sector. Stakeholder's acceptance significantly influences the successful introduction of LNG. This paper examines the determinants of LNG acceptance. A causal model based on the technology acceptance framework is suggested and a structural equation model was estimated. Political implications are discussed to provide an insight which measures are effective to support the introduction of LNG as an alternative fuel. Results suggest that LNG as an alternative fuel can be fostered by stimulating demand, increasing the availability of LNG and improving the ecological effects of the fuel technology. Highlights: The Technology Acceptance Model is applied to LNG as an alternative fuel. Accessibility, attitude, usability and usefulness influence the acceptance of LNG. A policy roadmap for the introduction of LNG is presented. LNG demand, availability and ecological effects should be addressed by politics.